On the differential аnd total asymmetry of the Fraunhofer lines in the solar spectrum - Kuli-Zade, D.M.; Basal, M.; Kandemir, С. (Кинематика и физика небесных тел, 1995)
A new quantitative method, recently proposed by Kuli-Zade, for the determination of the differential and total asymmetry of weak and medium strength Fraunhofer lines in the solar center spectrum, has been introduced. This method makes it possible to determine the asymmetry of the lines, and their variations in the line profiles, quantitatively and in energy units. Викладається недавно запропонований Кулі-Заде новий кількісний метод визначення диференціальної і загальної асиметрії слабких та помірних фраунгоферових ліній в спектрі центра сонячного диску. Цей метод дозволяє кількісно визначати асиметрію ліній і її зміну по профілю лінії. Излагается недавно предложенный Кули-Заде новый количественный метод определения дифференциальной и общей асимметрии слабых и умеренных фраунгоферовых линий в спектре центра солнечного диска. Этот метод позволяет количественно определить асимметрию линий и ее изменение по профилю линии.